PENGARUH MINAT BACA DAN PENGUASAAN KOSA KATA TERHADAP KETERAMPILAN MENULIS EKSPOSISI - widiyarto, sigit (JURNAL PESONA, 2017)
Interest in writing in general is still low. If we compare the number of journals in Indonesia with Malaysia and Thailand still lack . The low of students ability in scientific writing them due to lack of interest in reading and low mastery of vocabulary. The purpose of this study to determine the effect of the interest in reading writing skills, vocabulary mastery of the skill of writing and reading, and vocabulary mastery together against this writing. The study Â using quantitative methods, with the prerequisite test of normality, linearity and homogeneity. The results showed that: 1) there is no influence interest in reading the writing skills of exposition, 2) There is a significant relationship between vocabulary mastery of the writing skills, and 3) there are significant interest in reading and mastery of vocabulary jointly affect the writing skills exposition